Empowering Vocational Students: Teaching Informatics and Computer Skills at SMK Santo Gabriel Maumere - Jeja, Francis Assisi; Islamiyah, Mufidatul (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: To develop effective teaching strategies that keep up with technological advancements and meet student needs, ensuring they gain practical and comprehensive knowledge in informatics and computers. These strategies aim to equip students with the skills and knowledge needed for academic success and future careers in technology. Method: This study uses a student-centered approach, focusing on teacher-student interaction and the use of technology in teaching. Data is collected through student feedback on teaching methods and interviews with teachers and staff. The data is analyzed to evaluate the effectiveness of informatics and computer teaching at SMK Santo Gabriel Maumere. Practical Application: Provide guidance for teachers at SMK Santo Gabriel Maumere to improve the effectiveness of informatics and computer teaching. With better teaching methods, teachers can create more engaging and interactive strategies, helping students better understand technology. Conclusion: The teaching methods for informatics and computers at SMK Santo Gabriel Maumere need improvement for better results. Combining qualitative and quantitative evaluations offers valuable insights into teaching performance and guides future curriculum development.